Complicated Grief: How is it Conceptualized by Professionals?. Issue 1 (2nd January 2021) - Dodd, Anne; Guerin, Suzanne; Delaney, Susan; Dodd, Philip
Abstract: Despite the proliferation of grief research, there is no consensus regarding the naming of grief that does not follow a typical trajectory. How a concept such as grief that has become complicated, is named and understood will likely influence professionals' engagement with it. Professionals ( n  = 185; 71.8% female; mean age 51.9 years; SD = 8.9) defined complicated grief in a free-text box, within a survey. Statistically significant differences were found regarding extended duration, being stuck, and the circumstances surrounding the death. The differences in professionals' views of complicated grief and its multidisciplinary nature underscore the need for consensus regarding its nomenclature and definition.